2019
DOI: 10.3159/torrey-d-18-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Herbivory Rates and Leaf Phenology in Invasive and Native Shrubs in an East-Central Indiana Forest1

Abstract: Exotic species that become invasive can have a strong impact on the success of native species because of traits that enhance their competitive abilities. This study investigates three potential trait differences between common invasive and native shrubs that could enhance the competitive success of invasives: resistance to herbivory, length of autumn leaf retention, and timing of spring leaf emergence. We measured herbivory per plant by leaf-chewing insects, autumn leaf color change and retention, and spring l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For example, if human disturbance provides an opening for introduced species, such species should be short in stature, short‐lived, and highly fecund, in order to succeed in regional competition (via enhanced dispersal) while losing in local competition for photosynthetic resources (Givnish, 1982b; Platt and Weis, 1985). But some introduced species may spread because they bear novel anti‐herbivore or anti‐pathogen defenses (Keane and Crawley, 2002; Mitchell and Power, 2003; DeWalt et al, 2004; Cappuccino and Carpenter, 2005; Bodawatta et al, 2019; but see Schultheis et al, 2015) or novel anti‐competitor weapons (Bais et al, 2003; Callaway and Ridenour, 2004; Rudrappa et al, 2007; Callaway et al, 2008; Lankau et al, 2009; Evans et al, 2016)—their success is tied not to disturbance but to eco‐evolutionary novelty per se (Simberloff et al, 2012; Seabloom et al, 2015). Many such species—like Rhamnus cathartica and Typha angustifolia —are tall, long‐lived, and/or woody, and thereby can succeed in local competition against native species for photosynthetic resources in less disturbed sites after their novel defenses or weapons give them an initial edge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if human disturbance provides an opening for introduced species, such species should be short in stature, short‐lived, and highly fecund, in order to succeed in regional competition (via enhanced dispersal) while losing in local competition for photosynthetic resources (Givnish, 1982b; Platt and Weis, 1985). But some introduced species may spread because they bear novel anti‐herbivore or anti‐pathogen defenses (Keane and Crawley, 2002; Mitchell and Power, 2003; DeWalt et al, 2004; Cappuccino and Carpenter, 2005; Bodawatta et al, 2019; but see Schultheis et al, 2015) or novel anti‐competitor weapons (Bais et al, 2003; Callaway and Ridenour, 2004; Rudrappa et al, 2007; Callaway et al, 2008; Lankau et al, 2009; Evans et al, 2016)—their success is tied not to disturbance but to eco‐evolutionary novelty per se (Simberloff et al, 2012; Seabloom et al, 2015). Many such species—like Rhamnus cathartica and Typha angustifolia —are tall, long‐lived, and/or woody, and thereby can succeed in local competition against native species for photosynthetic resources in less disturbed sites after their novel defenses or weapons give them an initial edge.…”
Section: Discussionmentioning
confidence: 99%
“…Some introduced ornamental plants may be preferred horticulturally because they are considered pest free, meaning that insects, fungi, and other herbivores do not exploit them as food or shelter. This is supported by a recent study showing that native plants have significantly greater leaf herbivory rates than introduced invasive species (Bodawatta et al 2019). A 1999 study showed that 96% of North American terrestrial birds rely on insects to feed their young (Tallamy 2007), but if the plants preferred by insects (native) are not there, the birds will suffer.…”
mentioning
confidence: 87%